A change in the time-varying correlation between oil prices and the stock market. Issue 7 (16th April 2019) - Jones, Paul M.; Collins, Luke
ABSTRACT: We investigate the time-varying correlation between oil prices and stock prices. Estimation results from a multivariate DCC-GARCH model reveal that the correlation has changed since the financial crisis. Historically, the correlation has been close to zero or slightly negative. However, the correlation changed to positive during the Great Recession and continued to be positive through the first half of 2017. We investigate the role quantitative easing played in this change in correlation using a threshold model.